Navigating the barley grain quality and nutrition maze through systems seed biology - Bahman Panahi; Hossein Mohammadzadeh Jalaly (Journal of Agriculture and Food Research)
Barley is one of the most widely consumed cereals in the world. It is a valuable source of protein, carbohydrate, and micronutrient fortification in human diets. The integration of systems biology with modern breeding techniques presents a comprehensive approach to enhance the quality of barley seeds. Furthermore, the discovery of numerous distinct co-expressed gene modules each characterized by unique expression profiles and encompassing a wide range of candidate regulators, illuminates the complex nature of gene regulation during seed germination. This review also explores these mechanisms and the complex processes governing grain quality and nutrition in barley. The importance of target genes such as HvCslF6, HvMYB61, HvMYB46/83, HvSSI, HvFLO6, and HvISA1 in altering the regulation of grains quality and nutritional attributes was also emphasized in this review. These candidate genes represent valuable targets for breeding programs seeking to enhance protein content and addressing micronutrients deficiencies in human diet.